La2NiSb - A ternary ordered version of the Bi3Ni type with highly polar bonding - Schaefer, Konrad; Isaeva, Anna; Ruck, Michael; Gerke, Birgit; Schwickert, Christian; Poettgen, Rainer (Zeitschrift für Naturforschung Section B-A Journal of Chemical Sciences, 2014)
The lanthanum-rich antimonide La2NiSb was synthesized by annealing a cold-pressed pellet of the elements in a sealed silica glas tube at 1120 K. La2NiSb was characterized by powder and single-crystal X-ray diffraction: ordered Bi3Ni type, Pnma, Z = 4, a = 825.6(3), b = 452.2(2), c = 1195.5(4) pm, wR = 0.0695, 856 F2 values, 26 variables. The nickel atoms form infinite zigzag chains (259 pm Ni-Ni) with trigonal-prismatic lanthanum coordination for each nickel atom. The antimony atoms cap the rectangular faces of the lanthanum prisms (336 pm La - Sb) and thereby coordinate also the nickel atoms (271 pm Ni - Sb). These rods run parallel to the b axis and form a herringbone pattern, similar to the FeB-type structure of GdNi. Although metallic conductivity is expected for La2NiSb from DFT-based band structure calculations, the real-space bonding analysis shows prominent localization of electrons on antimonide anions and positively charged lanthanum cations. The chain substructure is strongly bonded by polar covalent Ni - Sb and multicenter Ni - Ni interactions. The nickel atoms, which are involved in multicenter bonding with adjacent nickel and lanthanum atoms, provide a conductivity pathway along the prismatic strands. 121Sb Mössbauer spectroscopic data at 78 K show a single signal at an isomer shift of -7.62(3) mm s-1, supporting the antimonide character. La2NiSb shows weak paramagnetism with a susceptibility of 2.5 × 10-3 emu mol-1 at room temperature.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Antimonide; Chemical bonding; Crystal structure; Lanthanum; Metal-rich compound